Investigating the structure and interactions of quorum sensing proteins QsrI, QsrJ and QsrB integral to solvent production in Clostridium acetobutylicum - O'Hara, Louise (2024)
Clostridium acetobutylicum ATCC 824 is an industrially relevant organism that was historically used in biofuel production. Biobutanol, a fuel with potential relevance in future industry, is produced via ABE fermentation. Whilst ABE fermentation pathways are well understood, their precise regulation in response to external and internal stimuli is still being investigated. Ten putative RRNPP-like quorum-sensing systems (Qss) theorised to be regulators of solvent production were identified in Clostridium acetobutylicum ATCC 824. RRNPP-family quorum sensing systems typically consist of a quorum sensing receptor (Qsr) with an N-terminal helix-turn-helix (HTH) domain and a C-terminal tetratricopeptide repeat (TPR) region, and a downstream quorum-sensing peptide (Qsp), the latter of which interacts directly with its associated Qsr after maturation. QsrI and QsrJ were identified as orphan regulators due to their lack of downstream Qsp. It was also found that they act as master regulators that control major physiological and metabolic changes, as knockout mutations in either regulator result in negligible butanol production and loss of sporulation. QssB was also highlighted for further study due to QsrB knockout mutants producing a significantly higher butanol volume than the wild-type. The aim of this research was to successfully purify these three selected regulatory proteins in order to study the structures and binding mechanism involving QspB. This would potentially be relevant to future research on improving biobutanol production in industry. Due to protein homology in medically relevant species, this could be relevant to future medical research too. This thesis demonstrates successful purifications of recombinant QsrI and QsrJ, predominantly with the HTH domain excised. Results show that QsrI forms both a homodimer and a heterodimer with QsrJ, with evidence that the heterodimer forms preferentially. QsrJ, when purified alone, remains a monomer. This work demonstrates an optimised purification protocol for QsrB with the potential to improve the purification of all clostridial or otherwise closely related RRNPP-like quorum-sensing regulators. The new protocol recommends omitting nickel from the purification process due to evidence of nickel column leeching resulting in increased protein aggregation. The recombinant TPR region of QsrB was successfully purified. Results show that QsrB forms a flexible, compact, dimeric, globular protein. SAXS results were used to optimise an Alphafold predicted structural model of the dimeric QsrB TPR regions, providing what is likely the most accurate structure of QsrB to date. This model notably suggests a level of asymmetry in the QsrB binding sites. Attempts to crystallise the QsrB TPR region to determine its structure via x-ray crystallography resulted in quasicrystals, and further optimisation is required to grow crystals. Isothermal titration calorimetry (ITC) results suggest two QspB molecules bind to the QsrB dimer sequentially due to a strong first binding interaction (1.98e-9M) likely lowering the affinity by a factor of ~10 for the second binding interaction (2.64e-8M). The data show that the QsrB N212 – QspB3-9 W7 backbone interaction is essential to QsrB-QspB complex formation. Alanine replacement experiments suggest that all QspB peptide residue functional groups (excluding W5) show evidence of strengthening the first binding interaction. Conversely, the functional groups in the QspB T4 and G6 residues show evidence of weakening the second binding interaction. The QsrB residues K368 and Y219 also play a role in weakening the second binding interaction. QsrB showed no evidence of binding to synthetic QspA & QspC-H, suggesting binding is highly specific, although changing just one residue in QspE (QspE-D4T) induced binding to QsrB. Additionally, the C. felsineum 7320 peptide, which was established as not functional in vivo, showed evidence of binding to QsrB, as did the C. felsineum 794 and C. acetobutylicum GXAS18-1 peptides. Thermal stability assay experiments show that QspB addition significantly increases the thermostability of the complex by 21.8°C compared to QsrB alone. Of all the different peptides and mutations included in this study, none matched the thermostability of the wild-type complex. In summary, this thesis initialises the in vitro research of clostridial RRNPP-like proteins, establishing a potential binding mechanism, essential amino acid interactions and an optimised predicted structural model of QsrB.